Grasping Arabic Terms of ‘Maqasid Syariah’ via Online Learning on Bitcoin in Post-Pandemic among Learners in Malaysia - Mohd Sham, Kamis; Muhammad Nazir, Alias; Damien, Mikeng (Science China Press, 2024)
As the use of language terms plays a more and more crucial role in economic movements with the globalization of the world economy, there is rising curiosity in the relationship between language and economic view. Undeniably, the literature connected to this field is growing rapidly in this world. Related to this issue, online learning also includes a spectrum of technologies such as email, the world wide web, chat, new groups and texts, and video conferencing in the field of education. This type of online learning supports learners in understanding their swiftness, according to their flexibility. The focus of education is the key to success in academic opportunities. Education has many benefits for individuals. The purpose of this study is to grasp the Arabic terms of Maqasid Syariah via online learning using bitcoin in the post-pandemic among learners in Malaysia. The objectives of the study are; a) explore individual views from students focusing on problems in understanding terms in Maqasid Syariah related to bitcoin via online learning during the post-pandemic era and b) assess the level of readiness among Malaysian learners regarding understanding Arabic terms in Maqasid Syariah related to bitcoin via online learning during the post-pandemic era. The research methodology in this study is based on an exploratory design that includes quantitative and qualitative data collection sources. For students, moving from conventional classrooms and engaging in face-to-face activities to online learning in a virtual classroom makes learning methods radically vary in other modes.